Liability of legal persons for the creation of criminal associations and participation in them by the legislation of Ukraine and other countries - Вознюк, Андрій Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article presents a comparative analysis of the liability of legal persons for the creation of criminal associations and participation in them under the laws of Ukraine and other countries. It was established that today we have a de facto mechanism for liability of legal persons in the case of certain crimes which are not de jure criminal liability. It is to some extent helps to prevent crimes committed in the interests of legal entities and has the potential to become an integral element of damages caused by the crime. Proposed extend in CC Ukraine grounds application to the legal entities measures of criminal law cases by crime under Art. 255 and 257 of the Criminal Code of Ukraine. In this regard, p. 4 h. 1 art. 96-3 CC Ukraine offer after words "Article 160," to supplement the numbers "255, 257".Proven in expedience to limit quasi criminal liability of legal persons committing the crime for the benefit of a legal person, if it led obtaining unlawful benefit or created the conditions for such benefits or purported to avoidance the statutory responsibilities inappropriate to because in the interests of legal entities can be committed crimes involving not only unlawful profits, for example, to the physical destruction of victims. Definitely obtaining unlawful benefit the most common, but not the only purpose of committing crimes for the benefit of a legal person. Do not limit other possible options and avoidance the statutory responsibilities. In connection with this offer note 2 to the art. 963 Criminal Code of Ukraine after words.